IMPLEMENTASI PROGRAM BANTUAN BAGI PELAKU UMKM TAHUN 2022 PADA LEMBAGA AMIL ZAKAT SWADAYA UMMAH KOTA PEKANBARU - Wahyuningsih, Endah (Komunitas Manajemen Kompetitif, 2024)
Zakat is a source of funding that is very important for helping the needs of lower class people, both related to social and economic needs. Zakat is given to those who are entitled in the form of 8 asnaf as stated in the Qur'an. One of the roles of zakat is to reduce poverty and unemployment. Zakat funds cannot be used only for consumer needs but also increasing benefits in the form of assistance for small and micro businesses.It is hoped that the benefits will be able to increase the community's economic growth.This research aims to find out how to implement the assistance program for MSMEs in 2022 at the Amil Zakat Swadaya Ummah Institution in the city of Pekanbaru. For this, a zakat amil institution is needed, it can be coordinated to the collection and distribution of zakat funds. The research method used in this research is descriptive qualitative approach. The data collection techniques used by interview techniques and secondary data. The obstacles, implementation of zakat by helping to increase economic growth are caused by several factors, namely, knowledge about productive zakat is still minimum, understanding of muzakki is still limited to the consumptive use of zakat and the muzakki's trust is still low in Amil Zakat Institutions